Degradation of Proteins and Starch by Combined Immobilization of Protease, α-Amylase and β-Galactosidase on a Single Electrospun Nanofibrous Membrane - Cloete, William J.; Hayward, Stefan; Swart, Pieter; Klumperman, Bert (Molecules (Basel, Switzerland), 2019)
Two commercially available enzymes, Dextrozyme (α-amylase) and Esperase (protease), were covalently immobilized on non-woven electrospun poly(styrene-co-maleic anhydride) nanofiber mats with partial retention of their catalytic activity. Immobilization was achieved for the enzymes on their own as well as in different combinations with an additional enzyme, β-galactosidase, on the same non-woven nanofiber mat. This experiment yielded a universal method for immobilizing different combinations of enzymes with nanofibrous mats containing maleic anhydride (MAnh) residues in the polymer backbone.